MODB: a comprehensive mitochondrial genome database for Mollusca. (12th September 2021) - Qu, Jiangyong; Xu, Yanran; Cui, Yutong; Wu, Sen; Wang, Lijun; Liu, Xiumei; Xing, Zhikai; Guo, Xiaoyu; Wang, Shanshan; Li, Ruoran; Sun, Xiaoyue; Li, Xiang; et al.
Abstract: Mollusca is the largest marine phylum, comprising about 23% of all named marine organisms, Mollusca systematics are still in flux, and an increase in human activities has affected Molluscan reproduction and development, strongly impacting diversity and classification. Therefore, it is necessary to explore the mitochondrial genome of Mollusca. The Mollusca mitochondrial database (MODB) was established for the Life and Health Big Data Center of Yantai University. This database is dedicated to collecting, sorting and sharing basic information regarding mollusks, especially their mitochondrial genome information. We also integrated a series of analysis and visualization tools, such as BLAST, MUSCLE, GENEWISE and LASTZ. In particular, a phylogenetic tree was implemented in this database to visualize the evolutionary relationships between species. The original version contains 616 species whose mitochondrial genomes have been sequenced. The database provides comprehensive information and analysis platform for researchers interested in understanding the biological characteristics of mollusks. Database URL : http://modb.ytu.edu.cn/